DEVELOPING INTERCULTURAL COMPETENCE FOR EFFECTIVE ENGLISH LANGUAGE TEAChING - Arzieva, B.A. (SCIENCE and SOCIETY, 2025)
The article deals with integrating intercultural competence (IC) into English as a Foreign Language (EFL) instruction enhances students’ cultural awareness and communicative skills. Using a mixed-methods approach with students and teachers, the research implemented activities based on scientists frameworks over a semester. Results showed significant improvements in students’ IC, reflected in higher Intercultural Development Inventory (IDI) scores and qualitative feedback. The study emphasizes the importance of embedding IC in EFL curricula and training teachers to foster intercultural understanding, preparing learners for global communication.